2015
DOI: 10.1080/10548408.2014.957372
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Market Orientation (MO) and Tourism Small and Medium-Sized Enterprises’ (SMEs) Performance in Developing Countries: A Review of the Literature

Abstract: This paper aims to build a structured literature review of the field of market orientation and its impact on tourism small and medium-sized enterprises (SMEs) performance in developing countries. This literature review will present a comprehensive survey of market orientation (MO) published articles to facilitate good understanding of MO. It serves as an archive and aims to help the scholars and practitioners to explore, analyse, and develop a clear understanding about the different research points and methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 145 publications
(163 reference statements)
1
15
0
Order By: Relevance
“…As Narver et al (2004, p. 338) note, the more "the 'voice' of the target customer is brought into the organization and is acted upon, the better the performance of a business". Although some studies have found a negative or no association between MO and performance, it is generally accepted that such a relationship is significantly positive (Shah et al, 2015). Therefore, the following hypothesis is proposed: H1.…”
Section: Direct Effectmentioning
confidence: 98%
“…As Narver et al (2004, p. 338) note, the more "the 'voice' of the target customer is brought into the organization and is acted upon, the better the performance of a business". Although some studies have found a negative or no association between MO and performance, it is generally accepted that such a relationship is significantly positive (Shah et al, 2015). Therefore, the following hypothesis is proposed: H1.…”
Section: Direct Effectmentioning
confidence: 98%
“…In contrast, Inman et al (2011) employed economic and market understanding to measure the business performance, while Nawanir et al (2013) relied on profitability, sales (share and growth and customer satisfaction. Overall, the approaches used by these studies is in line with the notion that business performance is a multidimensional construct, and therefore the use of composite measures is deemed appropriate (Shah et al, 2015).…”
Section: Service Quality Customer Acquisition Efforts and Business Performancementioning
confidence: 92%
“…To cope and survive the challenges of CPEC and vision 2020, this important sector needs to continuous learn from external environment and align itself with the outside changes. Especially the SME's working in tourism sector need to give more attention to their competitive advantage hence ensuring better performance (Shah, El-Gohary, & Hussain, 2015).…”
Section: Resultsmentioning
confidence: 99%